2020
DOI: 10.15171/hpp.2020.08
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Chikungunya disease personal protective behaviors: Results of a cross-sectional survey of US-Caribbean travelers

Abstract: Background: Incidents of vector-borne disease have recently tripled in the United States. Chikungunya disease is a particularly common disease in the Caribbean, posing a threat to international tourists. However, the relationship between psychological variables derived from the protection motivation theory (PMT), and adoption of protective behaviors against the disease, is uncertain. This study sought to identify the psychological predictors of travelers’ protective health behaviors, specifically (1) appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…These studies confirm earlier research that stipulates a positive relationship between self-efficacy and individual self-protection during travel (e.g. Anderson et al, 2020;Wang et al, 2019). Therefore, we propose:…”
Section: Travel Intentionsupporting
confidence: 90%
See 1 more Smart Citation
“…These studies confirm earlier research that stipulates a positive relationship between self-efficacy and individual self-protection during travel (e.g. Anderson et al, 2020;Wang et al, 2019). Therefore, we propose:…”
Section: Travel Intentionsupporting
confidence: 90%
“…Zheng et al (2021) show that people who consider themselves self-efficacious will experience reduced travel fear and are motivated to protect themselves during travel. These studies confirm earlier research that stipulates a positive relationship between self-efficacy and individual self-protection during travel (e. g. Anderson et al, 2020, Wang et al, 2019. Therefore, we propose: H3a: Perceived self-efficacy will increase willingness to travel domestically.…”
Section: Individual Beliefs (Perceived Susceptibility Severity Self-efficacy) and Willingness To Travelsupporting
confidence: 88%
“…Finally, the study's findings provide further empirical support for PMT ( Floyd et al, 2000 ) by lending credence to the role of cognitive processes, comprising perceptions towards the pandemic and perceived efficacy, in facilitating protective behavior (i.e., health risk preventative behavior) and in turn career resilience. PMT has been applied predominantly to common health risk behaviors such as disease prevention ( Anderson et al, 2020 ) or vaccination uptake ( Ling, Kothe, & Mullan, 2019 ) and rarely to protective behaviors in a pandemic setting ( Nguyen-Phuoc, Oviedo-Trespalacios, Nguyen, Dinh, & Su, 2022 ; Tang, Chen, Lin, & Feng, 2021 ; Zheng et al, 2021 ). Our study applies this theory not only to a pandemic context but also to the tourism sector.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen of the 28 included studies originated from Africa, including West Africa [ 19 ] and ten specified countries: Ethiopia [ 20 , 21 ], Kenya [ 22 ], Madagascar [ 18 ], Malawi [ 23 ], Mali [ 18 ], Nigeria [ 18 , 24 , 25 ], Rwanda [ 26 ], Uganda [ 27 ], and Tanzania [ 28 ]. Ten studies came from the Americas, of which 6 were conducted in the United States [ [29] , [30] , [31] , [32] , [33] , [34] ], and one each in Canada [ 35 ], Mexico [ 36 ], French-Guiana [ 37 ], and the Caribbean Island Curacao [ 38 ]. Three studies were conducted in Malaysia [ [39] , [40] , [41] ], one in the border region of Myanmar with Thailand [ 42 ] and another in Australia [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies which formed one record, focused solely on women with children under five years old [ 18 ]. Three studies focused on US travelers, outside of the US in general [ 31 ], and in Caribbean destinations in particular [ 29 , 32 ]. One study specifically examined adults with a confirmed chikungunya infection [ 38 ].…”
Section: Resultsmentioning
confidence: 99%